Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1212/wnl.0000000000007148
|View full text |Cite
|
Sign up to set email alerts
|

Statins do not increase risk of polyneuropathy

Abstract: Objective To investigate whether there is an association between cholesterol-lowering medication use, specifically statins, and chronic polyneuropathy. Methods A literature study was carried out to assess the current state of evidence on the association between chronic polyneuropathy and cholesterol-lowering medication use. We also conducted a prospective case-control study to compare exposure to cholesterol-lowering medication between patients with cryptogenic axonal polyneuropathy and controls prior to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Statin use has been associated with a 35% lower risk of amputation in the elderly population [93]. In a literature review of 13 studies Warendorf et al found that the odds of polyneuropathy reduced with increasing time exposure to statins [94] whilst Davis et al showed that statin usage reduced incident polyneuropathy by 35% in dose dependent manner [95]. However, other studies have failed to report a protective effect of statins on neuropathy [90,[96][97][98].…”
Section: Lipid Therapeutics Targeting Neuropathymentioning
confidence: 99%
“…Statin use has been associated with a 35% lower risk of amputation in the elderly population [93]. In a literature review of 13 studies Warendorf et al found that the odds of polyneuropathy reduced with increasing time exposure to statins [94] whilst Davis et al showed that statin usage reduced incident polyneuropathy by 35% in dose dependent manner [95]. However, other studies have failed to report a protective effect of statins on neuropathy [90,[96][97][98].…”
Section: Lipid Therapeutics Targeting Neuropathymentioning
confidence: 99%
“…All subjects underwent measurements in the University Medical Center Groningen (UMCG) as part of the TransplantLines Biobank and Cohort study, in which the living kidney donors serve as healthy controls [10]. We collected data on age, sex, height, weight, medical history, medication use [11][12][13], and co-morbidities from hospital records of the donor screening. Subjects were included between June 2016 and October 2017.…”
Section: Participantsmentioning
confidence: 99%